2019
DOI: 10.1093/cz/zoz063
|View full text |Cite
|
Sign up to set email alerts
|

Age structure of a lizard along an elevational gradient reveals nonlinear lifespan patterns with altitude

Abstract: Lifespan is one of the main components of life history. Shorter lifespans can be expected in marginal habitats. However, in the case of ectotherms, lifespan typically increases with altitude, even though temperature—one of the main factors to determine ectotherms’ life history—declines with elevation. This pattern can be explained by the fact that a shorter activity time favors survival. In this study, we analyzed how lifespan and other life-history traits of the lizard Psammodromus algirus vary along a 2,200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…The femurs, humeri, and phalanges have better consistency and resolution than the other bones. This result is also consistent with previous findings in other species (Castanet, 1994; Comas et al, 2020; Guarino et al, 2019; Lu et al, 2018; Santoyo‐Brito et al, 2018; Smirina & Ananjeva, 2007). Although age could be underestimated by LAGs in phalanges, it only occurs in a few very‐old individuals (Table 1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The femurs, humeri, and phalanges have better consistency and resolution than the other bones. This result is also consistent with previous findings in other species (Castanet, 1994; Comas et al, 2020; Guarino et al, 2019; Lu et al, 2018; Santoyo‐Brito et al, 2018; Smirina & Ananjeva, 2007). Although age could be underestimated by LAGs in phalanges, it only occurs in a few very‐old individuals (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…This inference is confirmed by the results reported previously (Lu et al, 2018). However, this result differs from the pattern prevalent in reptiles wherein populations from higher altitudes generally have higher longevity (Comas et al, 2020;Sindaco et al, 2010;Wapstra & Swain, 2001). Furthermore, Lu et al (2018) also indicated that the high-elevation population has shorter longevity but a larger SVL, and the low-elevation population has longer longevity but a smaller SVL.…”
Section: Discussionsupporting
confidence: 72%
“…Psammodromus algirus is a medium-sized ground-dwelling lizard with a lifespan of 3-5 years [34]; it is widespread in Mediterranean landscapes of the Iberian Peninsula where high-intensity fires are common. Although it is a habitat-generalist species [35], it prefers habitats with low shrub cover [36].…”
Section: Methods (A) Study Systemmentioning
confidence: 99%
“…To test if as a result of the cleaning effect of fire, lizards in postfire conditions suffer less cumulative parasitic infections than those living in unburned areas, and considering the life expectancy of P. algirus (approx. 3 years [34]), we sampled lizards at five locations in which the time since fire was 2-4 years (hereafter, 'older' wildfires). In such cases, we counted the number of raised ventral scales of the lizards in order to estimate the level of parasitism in lizards that have spent most of their lives under postfire conditions.…”
Section: (B) Lizard Sampling and Parasite Quantificationmentioning
confidence: 99%
“…Acanthodactylus erythrurus is the biggest [up to 8 cm snout-vent length (SVL)] and most thermophilic species of the three (Belliure et al ., 1996 ; Verwaijen and Van Damme, 2007 ). Although little is known about the exact life span of the species in the wild, the results of several studies allow to order the species from shorter to longer expected life span (Carretero and Llórente, 1991 ; Drechsler and Monrós, 2019 ; Comas et al ., 2020 ). Following this statement, A. erythurus has an intermediate life span, which is not known in detail, but the results in Drechsler and Monrós ( 2019 ), with 80% yearly renewal indicate that it seems to be around two years for most individuals in this population.…”
Section: Introductionmentioning
confidence: 99%